Performance characteristics of generic bell 206b helicopter tail rotor blade using empirical numerical method - Mahamad, Firdaus (2015)
This paper presents the Empirical Numerical Method for the analysis of the performance characteristics of a generic bell 206B helicopter tail rotor blade. The airfoil profile of the blade is near similar to NACA 0012 series, with maximum thickness 12% at 33% chord. This analysis work deals with the comparative study of variation in an angle of attack over the blade at different speed which using the software programming application that developed based on this empirical method. The analysis results were validated by comparing with the experimental results that had already done previously at Universiti Teknologi Malaysia _ Low Speed Tunnel (UTM-LST). The empirical method applied in this study was successfully able to obtain an optimal set of parameters for performance characteristics of the tail blade.